2016
DOI: 10.1210/en.2016-1608
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor in the Ovary Theca Cells Plays a Critical Role in Androgen-Induced Reproductive Dysfunction

Abstract: Androgen and its receptor (AR) play a critical role in reproductive function under both physiological and pathophysiological conditions. Female AR global knockout mice are subfertile due to both neuroendocrine and ovarian defects. Female offspring from prenatally androgenized heterozygous AR pregnant mice showed rescued estrous cyclicity and fertility. Ar is expressed in granulosa cells, theca interstitial cells, and oocytes in the ovary. We created mice with theca-specific deletion of Ar (ThARKO) by crossing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…Due to the interconnected nature of the hypothalamic-pituitary-gonadal axis, effects of excess androgens could be exerted at multiple levels of the axis (22,32). While some androgen effects occur in the brain, as reported by others (32, 33), whether ARs in gonadotropes contribute to the dysregulation of female estrous cycles and gonadotropin secretion is unknown.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Due to the interconnected nature of the hypothalamic-pituitary-gonadal axis, effects of excess androgens could be exerted at multiple levels of the axis (22,32). While some androgen effects occur in the brain, as reported by others (32, 33), whether ARs in gonadotropes contribute to the dysregulation of female estrous cycles and gonadotropin secretion is unknown.…”
mentioning
confidence: 98%
“…
women with PCOS (4,[24][25][26][27][28][29][30]. Notably, the 2xDHT mice do not exhibit alterations of basal serum estradiol, testosterone, or luteinizing hormone (LH); do not develop obesity; and show similar ovarian weight, serum levels of cholesterol, free fatty acids, leptin, TNFα, and IL-6 relative to controls even up to 3.5 months after DHT insertion (21,22,31).Due to the interconnected nature of the hypothalamic-pituitary-gonadal axis, effects of excess androgens could be exerted at multiple levels of the axis (22,32). While some androgen effects occur in the brain, as reported by others (32, 33), whether ARs in gonadotropes contribute to the dysregulation of female estrous cycles and gonadotropin secretion is unknown.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that 5a-dihydrotestosterone treatment to the rodent generated PCOS-like phenotypes, such as disturbing the estrous cycle and obesity (34,35). Recently, Ma et al (36) reported that the theca cell-specific androgen receptor (AR) KO mice show a reduced response to excess 5a-dihydrotestosterone and lack PCOSlike phenotypes. This suggests that the overproduced testosterone in theca cells could affect the estrous cycle through AR in theca cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while the nonaromatizable androgen DHT can be used, this is also not ideal as DHT is irreversibly metabolized to 3β-diol which interacts with ERβ permitting ER-mediated estrogen-like effects to occur [10, 11]. In the early 2000s, several global AR knockout (ARKO) female mouse models were generated [12-14], followed by a range of cell-specific ARKO female mouse models (granulosa cells and oocyte [15]; granulosa cells [16]; pituitary [17]; theca cells [18]) which have collectively proved a key role for androgen actions mediated via the AR in optimizing female fertility and reproductive function.…”
Section: Introductionmentioning
confidence: 99%